2003
DOI: 10.1161/01.hyp.0000055015.39788.29
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Level Is Associated With Elevated Blood Pressure in Blacks

Abstract: Abstract-Chronic lead exposure has been associated with elevated blood pressure in epidemiological studies. It is not known whether the previously observed relation between blood lead and hypertension persists after significant reductions have been made in environmental lead contamination. We examined the relation between blood lead levels and blood pressure in a representative sample of 14 952 whites and blacks aged 18 years or older who participated in the Third National Health and Nutrition Examination Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 61 publications
3
82
1
1
Order By: Relevance
“…Although significant progress has occurred regarding environmental contamination, there are still serious problems produced by heavy metals. The positive correlation between plasma lead concentration and hypertension (6)(7)(8), one of the most prominent cardiovascular problems in many countries, and the increase of all-cause mortality, including circulatory and cancer mortality (5), reinforce the biological significance of lead as an important hazard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although significant progress has occurred regarding environmental contamination, there are still serious problems produced by heavy metals. The positive correlation between plasma lead concentration and hypertension (6)(7)(8), one of the most prominent cardiovascular problems in many countries, and the increase of all-cause mortality, including circulatory and cancer mortality (5), reinforce the biological significance of lead as an important hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing data from the Third National Health and Nutrition Examination Survey (NHANES, 1988(NHANES, -1994, a positive correlation was reported between plasma lead concentration and arterial pressure in black men and women (8).…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no evidence of a threshold of critical lead induced-effects. The last PTWI value of 25 µg/kg/week was withdrawn following data from several epidemiological studies on neurodevelopment in children [16] and systolic blood pressure in adults [17][18][19][20]. However this withdrawn value is still being used by some authors for health risk assessments [7,21]; hence the value was used in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…However, an increase in arterial pressure has been reported for individuals with blood lead concentrations of 31.4 and 53.5 µg/dL (35)(36)(37). Previous studies on lead toxicity have reported 42.5 ± 2.3 and 58.7 µg/dL (38,39), blood concentrations that are similar to those found in the occupationally exposed population.…”
Section: Leadmentioning
confidence: 86%
“…In addition, chronic exposure to low levels of lead causes hypertension in animals and humans (33,34). Vupputuri et al (35), when re-evaluating the results of the Third National Health and Nutrition Examination Survey (36), reported a positive correlation between plasma lead concentration and arterial pressure in black men and women.…”
Section: Leadmentioning
confidence: 99%